Volumetric Analysis of Different Obturating Techniques Using CBCT: An In-vivo Study - Rahul Kappedath Kuttikkottil; Aayasha Sangal; Haritha Babu; Nikhil Puri; Varsha Maria Sebastian; Vipin Chembuzha Krishnadas; Tisson Varghese Job (Journal of Pharmacy and Bioallied Sciences)
Introduction: Root canal obturation is a critical phase in endodontic therapy, aimed at preventing reinfection and ensuring long-term therapeutic success. The quality of obturation is determined by the ability of the filling material to effectively seal the root canal system, preventing microbial invasion and minimizing the risk of recurrent infection. Various obturation techniques, including Cold Lateral Condensation, Carrier-Based, Thermoplasticized Injectable, and Cold Free-Flow Compaction, are employed, each with distinct advantages and disadvantages in terms of material adaptation, ease of application, and the potential for void formation. Methodology: This study utilized Cone Beam Computed Tomography (CBCT) for a comprehensive volumetric examination of the four root canal obturation techniques. CBCT was used to assess the material’s ability to fill the root canal space and identify the presence of voids, which could compromise the effectiveness of the obturation. Discussion: The Cold Lateral Condensation technique, while being cost-effective and easy to apply, may result in voids due to gaps between the gutta-percha cones. Other techniques, such as Carrier-Based and Thermoplasticized Injectable, offer improved adaptation and reduce the risk of void formation but may come with increased cost or complexity in application. Conclusion: The study underscores the importance of choosing an obturation technique that balances cost, ease of application, and material adaptation to ensure effective root canal sealing and minimize the risk of reinfection.